TRANSFORMASI MANAJEMEN PENDIDIKAN PESANTREN SALAFIYAH DI JAWA TIMUR: STUDI KUALITATIF DI PESANTREN LIRBOYO KEDIRI - Mochamad Arif Faizin (IAIN Kediri, 2015)
alafiyah in East Java. It was a qualitative research with an etnography method conducted in Pesantren Lirboyo,Â Kediri, in 2012. It focused on the transformation of the kyaiâ€™s leadership, educational methods, and institution.Â Pesantren Lirboyo is one of the pesantren salafiyahs in East Java that exists for more than 100 years. It showsÂ its great ability to survive survive, transform, and grow for a long period of time in which the leadership of theÂ kyai plays a very significant role. Therefore, this pesantren is worth examining. The article argued that theÂ transformation from single into dual, collective leadership in the pesantren has been able to reduce conflicts.Â The concepts of riá¸Ä, barakah, tawaá¸uâ€™ and taká¸im has been also encouraging the spirits to develop pesantrenbasedÂ model of educationKeywords: Pesantren, Salafiyah, Transformasi, Manajemen Pendidikan